2018
DOI: 10.1136/archdischild-2018-315648
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of recording and reviewing neonatal resuscitation: the providers’ perspective

Abstract: ObjectiveTo assess benefits of recording and reviewing neonatal resuscitation as experienced by neonatal care providers.DesignA qualitative study using semistructured interviews questioning neonatal care providers about their experiences with recording and reviewing neonatal resuscitation. Data were analysed using the qualitative data analysis software Atlas.ti V.7.0.SettingNeonatal care providers working at neonatal intensive care units (NICUs) of the Leiden University Medical Center, the Netherlands, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Successful audits require a safe learning environment. Important prerequisites for a safe learning environment include a blame-free, shame-free environment focusing on the benefits for learning and improving, proper information about the goal of audits, involvement of providers, and secured storage of recordings ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful audits require a safe learning environment. Important prerequisites for a safe learning environment include a blame-free, shame-free environment focusing on the benefits for learning and improving, proper information about the goal of audits, involvement of providers, and secured storage of recordings ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reported that providers report various educational benefits of auditing recordings of neonatal stabilization and that providers consider audits beneficial for improving the quality of care provided during neonatal transition. Providers, therefore, not only recommend the implementation of plenary audits but also acknowledge that successful implementation requires that audits should complement the needs of a NICU (9). Based on experiences at our center, we argue that auditing neonatal stabilization is a valuable tool in improving patient safety and the quality of care provided during neonatal stabilization, as it can be used to identify and address various areas for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Auditing neonatal resuscitation allows providers to mutually provide feedback. Earlier we reported that providers would recommend other NICUs to implement audits, assuming that preconditions for a safe learning environment are met (32). Providers emphasized that audits should be blame and shame free, non-punitive, and focused on educational benefits, amongst others.…”
Section: Discussionmentioning
confidence: 99%
“…To produce maximum variation in the study sample, participants were selected through purposive sampling, that is, a non-probability sampling method that is commonly used in qualitative research to cover a range of potentially relevant perspectives 26. Inclusion of participants continued until thematic saturation was reached on providers’ perspectives on recording and reviewing neonatal resuscitation 23…”
Section: Methodsmentioning
confidence: 99%
“…However, as jurisdiction and guidance for deferred consent vary, actual experience with deferred consent for DR studies is limited and indepth understanding of providers’ views on deferred consent for DR studies is lacking 22. As part of a larger project,23 24 we conducted interviews with providers of neonatal intensive care units (NICUs) that participate in the same studies, but differ in their consent approaches. With this paper, we aim to gain insight into providers’ perceptions of deferred consent for DR studies in actual scenarios.…”
Section: Introductionmentioning
confidence: 99%